Is community management of resources by urban households, feasible? Lessons from community gardens in Gweru, Zimbabwe - Mwakiwa, Emmanuel; Maparara, Tendai; Tatsvarei, Simbarashe; Muzamhindo, Nolyn (Elsevier GmbH, 2021)
The poor economic situation in Zimbabwe has forced many households to engage in urban agriculture. With the increasing number of households engaging in the practice, a local NGO in 2009 introduced community gardens in the city of Gweru to vulnerable households as a new development initiative. We examine the feasibility of community resource management in these gardens using a blend of econometrics and community resource management theory. The study finds that sex of head of household, household labour, on-plot area, and off-plot area significantly affected the decision to practice community gardening. Results also show that households characterised by food insecurity tended to be the participants in community gardens. Strong social capital made it possible for these households to participate in community management of resources. However, there is need to remove obstacles such as uncertainty of tenure. Given the potential of urban agriculture in alleviating food insecurity, urban authorities need to consider their position that the practice causes river siltation and include it in their planning processes.